Effects of Intrinsic Flexibility on Adsorption Properties of Metal–Organic Frameworks at Dilute and Nondilute Loadings - Agrawal, Mayank; Sholl, David S (ACS applied materials & interfaces, 2019)
Molecular simulation of adsorption in nanoporous materials has become a valuable complement to experimental studies of these materials. In almost all cases, these simulations treat the adsorbing material as rigid. We use molecular simulations to examine the validity of this approximation for the adsorption in metal–organic frameworks (MOFs) that have framework flexibility without change in their unit cells because of thermal vibrations. All nanoporous materials are subject to this kind of framework flexibility. We examine the adsorption of nine molecules (CO2, CH4, ethane, ethene, propane, propene, butane, Xe, and Kr) and four molecular mixtures (CO2/CH4, ethane/ethene, propane/propene/butane, and Xe/Kr) in 100 MOFs at dilute and nondilute adsorption conditions. Our results show that single-component adsorption uptakes at nondilute conditions are only weakly affected by framework flexibility, but adsorption selectivities at both dilute and nondilute conditions can be significantly affected by flexibility. The most dramatic impacts of framework flexibility occur for adsorption uptake in the limit of dilute adsorption. These results suggest that the importance of including framework flexibility when attempting to make quantitative predictions of adsorption selectivity in MOFs and similar materials may have been underestimated in the past.